Pengembangan Penuntun Praktikum Perkembangan Hewan Berbasis Pendekatan Saintifik untuk Mahasiswa Jurusan Biologi - Diah Putri Anggun (Bioilmi: Jurnal Pendidikan, 2019)
In practical activities of animal structure subject, the students needed a handbook that can help them to master the materials through practice activities. Animal development practical handbook based on scientific approach could help students to increased their abilities and competencies in practice activities. The research aimed to describe the developmental process of practical handbook based on scientific approach and to produce a valid, practical, and effective handbook. The research used Plomp models which consisted three phase involving of preliminary research, development or prototype, and assessment phase. The instruments of data collection were obtained from handbook validity sheets, practicality questionnaires for lecturers and students, and observation sheets in order to see the students’ competencies (cognitive and psychomotor aspects). The field test was done by 41 biology students at UIN Raden Fatah Palembang. The data was analyzed descriptively and statistically. The results of the research show us that animal structure practical handbook based on scientific approach is very valid. It meant that the practical handbook has a good quality based on the assessment from the expert of content, constructive, technique, and language. The lecturers and students categorized this handbook as very practical since it is easy to used. The handbook was categorized as effective because the experiment class shows the increasing of their competencies at cognitive, affective, and psychomotor aspects. It is because the students could follow the phases of scientific approach well. Thus, it could be said that the animal structure practical handbook based scientific approach that has been developed was valid, practical, and effective. Keywords — handbook, scientific approach, animal structure, plomp models, validation, practicalities, effectiveness, student competences.